PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT INTERTAMA TRIKENCANA BERISNAR MEDAN - Fransiska L Nababan; Bimantara Sembiring; Lika Bancin; Lilis Sianturi; Maya Agustina Tanjung (Jurnal Darma Agung, 2020)
The study aims to determine the effect of leadership, motivation, and competence on employee performance at PT Intertama Trikencana Bersinar Medan, both partially and simultaneously. The research method uses quantitative descriptive analysis. The population in the study were all employees in a total of 165 people. Data analysis techniques using the F Test, T Test, and Multiple Linear Regression. Based on the results of data analysis in research shows partially it can be seen that leadership (X1) has a tcount of 1,589 and a ttable value of 1.658, then a tcount <ttable (1,589 <1,658) and a sig.0.00 value <0,115. This means that the hypothesis is rejected, namely: partial leadership has no positive and significant effect on employee performance at PT Intertama Trikencana Bersinar Medan. The results showed that motivation (X2) had a positive and significant effect on employee work performance (Y) at PT Intertama Trikencana Bersinar. Where the motivation variable (X2) has a tcount of 2.511 and a ttable value of 1.658 then the value of tcount> ttable (2.511> 1.658) and a sig value. 0.00 <0.014. The results showed that competence (X3) had no positive and significant effect on employee work performance (Y) in PT Intertama Trikencana Bersinar. Where the Competency variable (X3) has a tcount of 1,498 and a ttable of 1,658 then the ttable value <ttable (1,498 <1,658) and sig. 0.00 <0.137.